Further Validation and Development of the Movement Imagery Questionnaire - Williams, S.; Cumming, J.; Ntoumanis, Nikos; Nordin-Bates, S.; Ramsey, R.; Hall, C. (Human Kinetics, 2012)
This research validated and extended the Movement Imagery Questionnaire-Revised (MIQ-R; Hall & Martin, 1997). Study 1 (N = 400) examined the MIQ-R’s factor structure via multitrait-multimethod confirmatory factor analysis. The questionnaire was then modified in Study 2 (N = 370) to separately assess the ease of imaging external visual imagery and internal visual imagery, as well as kinesthetic imagery (termed the Movement Imagery Questionnaire-3; MIQ-3). Both Studies 1 and 2 found that a correlated-traits correlated-uniqueness model provided the best fit to the data, while displaying gender invariance and no significant differences in latent mean scores across gender. Study 3 (N = 97) demonstrated the MIQ-3’s predictive validity revealing the relationships between imagery ability and observational learning use. Findings highlight the method effects that occur by assessing each type of imagery ability using the same four movements and demonstrate that better imagers report greater use of observational learning.